Malignant thymoma as etiology of bilateral, biventricular cardiac failure - Priester, P; Kopecky, J; Slovacek, L (Bratislavské lekárske listy, 2011)
The authors report on a case of a 60-year-old female admitted to hospital with symptoms of bilateral cardiac failure. Upon ultrasonic examination of the heart, a massive pericardial exudate was diagnosed. Pericardial drainage was done to find the cause of pericardial effusion. Cells of malignant lymphoma were detected cytologically while immunophenotypization demonstrated a malignant lymphoma exudate. A computed tomography (CT) examination of the thorax disclosed a mediastinal tumour with infiltration of both lungs, vascular structures and dissemination on the chest wall. A CT-guided tumour biopsy was performed to confirm or exclude a lymphoproliferative process. Histopathologically, an invasive cortical thymoma was verified. The tumour was evaluated as stage III thymoma according to Masaoka. This case report highlights a rare malignant thymoma, its clinical symptoms, diagnosis, therapy and prognosis (Fig. 2, Ref. 10).
Keywords: perikardiální efuze; thymom; Female; Thymoma; Humans; ženské pohlaví; Thymus Neoplasms; Heart Failure; lidé; srdeční selhání; lidé středního věku; Middle Aged; nádory brzlíku; Pericardial Effusion; Electrocardiography; elektrokardiografie